Optimised Application of the Microwave Extraction Technique of Essential Oils from Aquilaria Malaccensis Lamk Wood and Cymbopogon Nardus (L.) Rendle Leaves - Yahaya, Bibi Sabrina (2011)
In this study, the important process parameters such as microwave power, temperature and extraction time of MET are controlled to obtain the highest yield of extracted essential oil. The microwave extraction method for the essential oil from gaharu and citronella grass is compared with the conventional extraction technique (CET). In such a way to obtain the first droplet of distillation, it is necessary to heat up only 10 to 13 minutes with MET against 25 to 45 minutes with CET for Aquilaria malaccensis wood while for Cymbopogon nardus extraction, it requires 3 to 7 minutes for MET and about 12 to 20 minutes for CET to obtain the first droplet of oil. After 1 hour of extraction, MET gives higher percentage yield of oil with 0.016% for wet distillation for Aquilaria malaccensis and 1.21% for Cymbopogon nardus while the percentage yield of oil obtained by the CET is only 0.140% for Aquilaria malaccensis and 3.51% for Cymbopogon nardus after 8 hours of extraction. Another parameter is day of soaking for the samples. It plays an important role in the extraction where by the long time the sample was soaked, the more yield were collected. The highest yield was 0.116% which obtained in ten days of soaking. Identification of the chemical component was based on comparison of calculated retention indices and mass spectral data with literature values. The tested result of the oils showed some variation and differences in terms of GC profiles, concentration and chemical derivatives. In gaharu essential oil, the composition of oil isolated by the hydro distillation (MET) is dominated by dodecanoic acid, ethenyl ester, lauric acid, and vinyl ester yielding 12.75%. while in citronella essential oil, the composition is dominated by 6-octenal, 3,7-dimethyl and citronellal yielding 24.68% This project is also looking for the various techniques of extraction process such as hydro (HD), dry (DD) and steam (SD) distillation techniques. The results from each technique were presented. The project has successfully proved that MET is more efficient than CET in terms of rapidity and the quantity of the yield.